Comparison of different carotid stent designs in endovascular therapy of severe carotid artery stenosis. Issue 1 (22nd June 2020) - Gruber, Philipp; Berberat, Jatta; Kahles, Timo; Anon, Javier; Diepers, Michael; Nedeltchev, Krassen; Remonda, Luca
Background: One of the major periprocedural risks of carotid artery stenting is embolism caused either by plaque debris or by local thrombus forming. Double-layer micromesh stent design has shown to lower the chance of debris embolism but might have a slightly higher risk of local thrombus forming. Thus, we compared two different stent designs regarding safety and outcome profile in elective patients with high-grade carotid artery stenosis using a self-expanding, double-layer micromesh carotid stent system (DLCS) or a self-expanding hybrid carotid stent system (HCS). Methods: A single-center, open-label, retrospective cohort study of 67 consecutive, elective patients with high-grade symptomatic and asymptomatic carotid stenosis was executed at a comprehensive stroke center. Outcome measures were reocclusion rate, periprocedural symptomatic ischemic events, as well as other periprocedural complications, and recurrent stroke and mortality at 30 days' follow-up. Results: Thirty-two patients (24% women, median age 75 years (interquartile range (IQR) 71–80) were treated with DLCS, and 35 patients (29% women, median age 71 years (IQR 63–76) years) with HCS. In both groups, pretreatment carotid stenosis degree was similar (median NASCET of 80%). Successful deployment was achieved in all cases without technical failure, and both groups did not differ in reocclusion rates, recurrent stroke, and mortality within 30 days. Conclusions: DCLS and HCS revealed to have similar safety and outcome profile in elective patients with high-grade symptomatic as well as asymptomatic carotid artery stenosis.